The Effectiveness of Education about the First 1000 Days of Life for Early Mothers in Preventing Stunting - Yuliani, Eva; Nurmagandi, Boby; Sastriani, Sastriani; Lusiana, Lusiana (Poltekkes Kemenkes Gorontalo, 2024)
Stunting is a type of chronic malnutrition caused by a lack of nutrient intake for a long time, causing growth problems. One of the causes of stunting is early marriage, which has an impact on a mother's knowledge. Mothers, as primary caregivers for toddlers, must get sufficient information about how to optimize child growth and development in the first 1000 days of life so that they can help prevent stunting in children. The purpose of this study was to determine whether there was an effect of education on increasing the knowledge of early childhood mothers about preventing stunting in toddlers in the village of North Bonde. The research method used is pre-experimental design research with the type of one-group pretest posttest design. The sampling technique used is non-probability sampling by means of purposive sampling, so the samples used in this study amounted to 30. The results showed that before being given education, the number of mothers who had a good level of knowledge was 1 person (3.3%), mothers with a fair level of knowledge were 6 people (20%), and those with a poor level of knowledge were 23 people (76.7%). After being given education, there were 9 mothers with a good level of knowledge (30%), 12 mothers with a fair level of knowledge (40%), and 9 mothers with a poor level of knowledge (30%). the average knowledge before being given education was 46.00, after being given education there was an increase in the average knowledge to 64.50. In the results of the analysis of the marginal homogeneity test, it was found that education has an effect on increasing the knowledge of early childhood mothers about stunting prevention among toddlers in North Bonde Village. It is recommended for respondents to be more active in seeking information and increasing their knowledge from both the media and health workers regarding stunting prevention.